Analisis Pengaruh Komponen Relationship Marketing terhadap Kepuasan dan Loyalitas Konsumen - Linda Purwanti; Ria Fitri Mawardiningrum (BADAN PENERBIT STIEPARI PRESS, 2021)
This study aims to analyze the effect of relationship marketing components on customer satisfaction and loyalty. Relationship marketing is an approach that focuses on building and maintaining long-term relationships with customers to increase the value received by both parties. In this study, we explore several key components of relationship marketing, including effective communication, trust, commitment, and personal interaction, and how each component affects customer satisfaction and loyalty. The research method used was a survey with questionnaires distributed to 250 consumers in the retail sector. The results of the analysis show that effective communication and trust have a significant effect on customer satisfaction, while commitment and personal interaction have a strong direct impact on customer loyalty. This research provides valuable insights for companies in designing relationship marketing strategies that can increase customer satisfaction and loyalty, which ultimately contribute to the long-term success of the company.